Pengabdian kepada Masyarakat Edukasi Membangun Lingkungan Positif, Menjaga Anak dari Pergaulan Buruk pada Panti Asuhan Pintu Elok Pamulang - Ussholikhah, Diah Anisa; Rafli, Muhamad; Rohyana, Sigit; Marni; Irenne Putren, S.Pd., M.Pd. (Universitas Pamulang, 2025)
This community service (PKM) is motivated by the children's vulnerability in the orphanage to negative associations, requiring structured intervention to build character defense. The partner problem is the need for a specific, applied prevention program at Pintu Elok Orphanage against negative behaviors. The main objective is to equip children with an in-depth understanding of the characteristics, impact, and refusal methods for bullying, school truancy, and playing until they lose track of time. The method combined detailed educational counseling with Role-Playing simulations and interactive games (